2009
DOI: 10.1002/acp.1542
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction in a survival environment

Abstract: Victims often respond to survival incidents with maladaptive behaviours that suggest impairment in executive function. To examine this hypothesis the authors tested sub-components of executive function during an intensive military survival exercise. Compared to a control group the survival course participants showed significant impairment in the incongruent condition of the Stroop task; the mean repetition gap and adjacent letter pair components of the random letter generation task; and the planning and action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…That is, problems whose solutions involved survival-related information were more readily primed by false memories than problems whose solutions involved neutral information and these effects were developmentally invariant. These results provide compelling evidence that false memories could have evolved to be as adaptive as true memories and that, like Porter and Leach (2010) have speculated, these problems are more easily primed because survival information affords a more rapid and enhanced access to information in memory, information that is necessary for insight-based problem solving.…”
Section: False Memories From Survival Processingmentioning
confidence: 60%
See 1 more Smart Citation
“…That is, problems whose solutions involved survival-related information were more readily primed by false memories than problems whose solutions involved neutral information and these effects were developmentally invariant. These results provide compelling evidence that false memories could have evolved to be as adaptive as true memories and that, like Porter and Leach (2010) have speculated, these problems are more easily primed because survival information affords a more rapid and enhanced access to information in memory, information that is necessary for insight-based problem solving.…”
Section: False Memories From Survival Processingmentioning
confidence: 60%
“…By this account, increased spreading activation caused by survival processing will be more rapid and efficient, providing enhanced access to both true and false memories during later problem solving (e.g. Porter & Leach, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that these effects are not due to differences in problem difficulty as we intentionally equated this dimension across neutral and survival CRAT problems. Perhaps, as Porter and Leach (2010) have speculated, these problems are more easily primed because survival information, both true and false, affords a more rapid and enhanced access to information in memory, information that is necessary for insight-based problem solving. Indeed, that spreading activation of information is enhanced when remembering or reasoning about information in a survival-related context may be important to adaptation and may well represent a critical evolutionary trait.…”
Section: Discussionmentioning
confidence: 99%
“…Howe and Derbish (2010;Howe, 2011) suggested that correlated increases in true and false memory rates for survival information arise because such information is more densely represented in memory, making spreading activation to related concepts (including list themes) more rapid and efficient, something that might have adaptive value. One such advantage might be the ability to solve problems more rapidly given enhanced access to information in memory in a survival-related context, something that may be a crucial evolutionary trait (see Porter & Leach, 2010).…”
mentioning
confidence: 99%
“…Cognitive function is also hindered under these conditions. Specifically, individuals exposed to 4 days of simulated 'aircraft down' had significant impairments in planning and selective attention (incongruent form of Stroop test) (Porter and Leach 2010).…”
Section: Introductionmentioning
confidence: 99%